2017
DOI: 10.1080/17549507.2017.1363290
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of receptive and expressive vocabulary development in children with Down syndrome

Abstract: A wide range of internal and external predictors for vocabulary development of children with DS was found. Predictors resemble those predicting vocabulary development in peers with typical development between 1 and 6 years of age, as identified in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…These factors are likely to be proxies for a constellation of more proximal variables, including the ways in which parents talk to, and interact with, their children. Understanding the pathways of influence of maternal education and perceived closeness will be important for designing individualized interventions that target parental behavior [77,78,113,114]. At the same time, however, it is important to recognize the bidirectional and dynamic nature of the youth with DS or FXS and the environment provided by parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are likely to be proxies for a constellation of more proximal variables, including the ways in which parents talk to, and interact with, their children. Understanding the pathways of influence of maternal education and perceived closeness will be important for designing individualized interventions that target parental behavior [77,78,113,114]. At the same time, however, it is important to recognize the bidirectional and dynamic nature of the youth with DS or FXS and the environment provided by parents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher levels of parental education are associated with better expressive language skills in TD children [72,73], as well as in individuals with ID [6,[74][75][76][77]. Studies focused on individuals with FXS or DS have also suggested a positive association of maternal education with expressive vocabulary outcomes after controlling for CA [78]. Not all of these studies, however, have controlled for differences in the children's cognitive level, which makes it difficult to interpret their findings because variability in children's language development is likely to be related to cognitive differences [8].…”
Section: Sources Of Variation In Expressive Language Development In Imentioning
confidence: 99%
“…That SES was not predictive in the current sample suggests that the DS genotype is the overriding influence. We should note that in their study of 48 3-year-olds with DS, Deckers et al (2017) reported age-corrected correlations of maternal education to expressive vocabulary of around 0.5, though curiously no effect was observed on receptive vocabulary. The disparity may arise due to the different sampling of SES ranges, so that SES is a reliable predictor where families with lower SES are included.…”
Section: Environmental Factors Influencing Early Vocabulary Developmementioning
confidence: 80%
“…At 6-month follow-up, the former child was still non-verbal, the latter producing nearly 500 words. Another longitudinal study of a sample of children with DS from 2 to 7 years, which used an 18-month follow-up period, charted growth varying from around 400 additional words, to children who verbally expressed only a few more words or even expressed fewer words at follow up ( Deckers et al, 2017 ). Poor speech intelligibility may affect productive language performance, which could explain some of the discrepancy between expressive and receptive language levels ( Miller & Leddy, 1998 ) and children with DS vary in the extent to which they exploit gesture as an alternative modality to support their communication ( te Kaat-van den Os et al, 2017 ).…”
Section: Environmental Factors Influencing Early Vocabulary Developmementioning
confidence: 99%
See 1 more Smart Citation